PSYCHOSOCIAL SUFFERING OF TRANSSEXUAL AND TRANSCENT POPULATIONS IN STREET CONDITIONS - Sousa Silva, Thallis; Felipe Rocha, Leonardo; de Souza Silva, Karen; Moura da Silva Acerbi, Julia; Francelino da Silva, Wemerson; Moreira Neumann, Marcelo (Revista Gênero e Interdisciplinaridade, 2021)
The article presents a discussion about the psychosocial suffering of transsexual and transvestite populations living on the streets. The research was carried out through a qualitative exploratory typology, based on a literature review on the subject, having been used as a basis 5 interviews - reports and reports - in audiovisual and written formats. The objective of the research is to understand the relationship between transsexuality and the experiences in the street in the constitution of psychosocial suffering. Some of the determinants that lead to homelessness were addressed; the experiences of this homeless population and the institutional movements that provide shelter and reception, with emphasis on the institution “Casa Florescer”, located in downtown São Paulo. From a socio-historical perspective of psychology, the profile of these people living on the streets in the city of São Paulo was drawn, and the processes of marginalization of this social and historically oppressed group were analyzed. Finally, from the analysis of the reports, it is concluded that the forms of treatment given by the community, family and institutions, are of wide influence to enhance the arrival of this population on the streets, as well as their permanence in this condition, which is still aggravated by the absence of effective public policies that should guarantee access to health and decent housing.